Maximum power control system for solar panels using the Sliding Mode Controller (SMC) method - Nugraha, Ksatria; Yuhendri, Muldi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Solar energy is a promising renewable energy source that offers solutions to the energy crisis and carbon emission reduction, but the power output generated by solar panels is fluctuating due to changes in light intensity and ambient temperature. This study develops a Maximum Power Point Tracking (MPPT) control system using the Sliding Mode Controller (SMC) method to optimize the power output of solar panels. The system design includes the use of a boost converter as a voltage regulator and an Arduino Mega 2560 microcontroller as the control center, with the SMC algorithm developed in Simulink MATLAB to generate a PWM signal that controls the duty cycle. Test results show that the SMC algorithm can achieve a maximum power point of 30 watts in 20 seconds, faster and more efficient than the Perturb and Observe (P&O) method, which only reaches 25 watts in 30 seconds, and demonstrates lower and more stable power oscillations. The boost converter was also proven effective in increasing the output voltage of the solar panel. Thus, the SMC-based MPPT system demonstrates superior performance in efficiency and adaptability to dynamic environmental conditions, making it suitable for application in the development of more reliable solar energy systems